Plato's Socrates on Socrates Socratic Self-Disclosure and the Public Practice of Philosophy - Schultz, Anne-Marie (Lexington Books, 2020)
Anne-Marie Schultz explores Plato's presentation of Socrates as a philosopher who tells narratives about himself in the Theaetetus, Symposium, Apology, and Phaedo. She argues that scholars should regard Socrates as a public philosopher, while examining Socratic self-disclosive practices in the works of bell hooks, Kathy Khang, and Ta-Neishi Coates.